Epidemiological data from the COVID-19 outbreak, real-time case information - Xu, B; Gutierrez, B; Mekaru, S; Sewalk, K; Goodwin, L; Loskill, A; Cohn, EL; Hswen, Y; Hill, SC; Cobo, MM; Zarebski, AE; Li, S; et al. (Springer Nature, 2020)
Cases of a novel coronavirus were first reported in Wuhan, Hubei province, China, in December 2019 and have since spread across the world. Epidemiological studies have indicated human-to-human transmission in China and elsewhere. To aid the analysis and tracking of the COVID-19 epidemic we collected and curated individual-level data from national, provincial, and municipal health reports, as well as additional information from online reports. All data are geo-coded and, where available, include symptoms, key dates (date of onset, admission, and confirmation), and travel history. The generation of detailed, real-time, and robust data for emerging disease outbreaks is important and can help to generate robust evidence that will support and inform public health decision making.